The Effect of Good Corporate Governance, Firm Age, and Leverage on Firm Value - Khaniya, Dhiyafara; Lapae, Kanaya; Santoso, Pramesti Wulandari (Research of Business and Management, 2023)
This study aims to investigate the impact of Good Corporate Governance, Firm Age, and Leverage on Firm Value. This study's sample consists of non-financial companies listed on the Indonesia Stock Exchange in the LQ45 Index from 2014 to 2018. This study relies on secondary data. The technique used for data analysis is quantitative analysis. Panel Data Regression with the Fixed Effect Model was used as the analytical method. The findings indicate that Good Corporate Governance by proxy of the Independent Board of Commissioners, Institutional Ownership, and the Audit Committee do not affect the Firm's value. Firm Age and Leverage, on the other hand, impact Firm Value.